Low-Intensity Shockwave Therapy in the Treatment of Erectile Dysfunction - Lurz, Kelly (Cureus, 2020)
Introduction Low-intensity shockwave therapy (LISWT) may improve erectile function in patients with mild to moderate erectile dysfunction (ED). Currently there is a paucity of research and prospective data on the utilization of LISWT in patients with ED. We present the results of our phase II clinical trial of LISWT with short-term follow-up in a cohort of patients with mild to moderate vasculogenic ED. Methods We obtained IRB approval and prospectively enrolled patients with mild to moderate vasculogenic ED. Baseline International Index of Erectile Function (IIEF) scores and peak systolic velocities (PSV) of cavernosal arteries measured on duplex penile ultrasound were obtained prior to treatment. Treatment included 6600 total shocks per session, for a total of six consecutive weekly treatment sessions. Baseline Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) scores were obtained at the completion of the treatment course. IIEF, EDITS and PSV were evaluated again at one-month follow-up. Clinical significance was defined as a median IIEF score increase of four points from baseline or an EDITS total score increase to greater than 65 or increase of greater than ten from baseline. Treatment success was evaluated on an individual basis and defined by a clinically significant improvement in questionnaire score. Results A total of 25 patients were enrolled in the trial, with 22 patients reporting for one-month follow-up. 68% (15/22) of patients demonstrated treatment success. In the cohort there was improvement in median EDITS from 61 (IQR 49-92) to 73 (IQR 43-49), which did meet criteria for clinical significance, but did not reach statistical significance (p = 0.74). IIEF improved from a median of 13 (IQR 12-19) to 18 (IQR 14-25), which did reach statistical significance (p = 0.011). On duplex ultrasound, mean cavernosal artery PSV increased from 34.3 cm/s (IQR 25.7-51.1) to 38.0 cm/s (IQR 31.6-45.1); however, these differences were statistically insignificant (p = 0.986). Of the 25 patients undergoing LISWT, two reported discomfort during treatment sessions, which subsided after repositioning the device without alterations in energy delivered. Conclusion LISWT may be a safe and potentially efficacious clinical modality for treatment of patients with mild to moderate vasculogenic ED demonstrating increases in cavernosal artery PSV and improvements in IIEF and EDITS scores in short-term follow-up. Longitudinal studies with increased power are needed to better evaluate the long-term efficacy and cost-efficiency of this therapy.